An Experimental Study of Granular Material Using Recycled Concrete Waste for Pavement Roadbed Construction - Al-Mosawe, Hasan; Albayati, Amjad; Wang, Yu; Mashaan, Nuha S (2022)
Rapid worldwide urbanization and drastic population growth have increased the demand for new road construction, which will cause a substantial amount of natural resources such as aggregates to be consumed. The use of recycled concrete aggregate could be one of the possible ways to offset the aggregate shortage problem and reduce environmental pollution. This paper reports an experimental study of unbound granular material using recycled concrete aggregate for pavement subbase construction. Five percentages of recycled concrete aggregate obtained from two different sources with an originally designed compressive strength of 20-30 MPa as well as 31-40 MPa at three particle size levels, i.e., coarse, fine, and extra fine, were tested for their properties, i.e., the optimum moisture content density, Californian bearing ratio, and resilient modulus. A characterization of the resilient modulus of the mixes under complex stress conditions was performed. The characterized modulus model was used in the nonlinear analysis of the pavement structure under traffic loading using KENALYER software. Consequently, the two critical responses, i.e., the tensile strain at the bottom of the asphalt layer and the vertical compressive strain at the top of the subgrade, were computed and compared for the pavement structures with varying types and percentages of recycled concrete aggregate used in the subbase layer.